Novi mediji urbanosti - Robert, Laurent-Paul (Urbani izziv, 2003)
The digital manifestations of city are internet communities, virtual cities and cyberspace as represented in computer games, virtual reality, computer visualisation, digital film etc. Representations of urban space in the new media provide a feedback to physical cities thus becoming a hybrid space.
Keywords: digitalna tehnika; kibernetski prostor; mesta; navidezna resničnost; navidezne skupnosti; računalniške igre